2018
DOI: 10.1038/s41598-018-22303-y
|View full text |Cite
|
Sign up to set email alerts
|

In silico screening for human norovirus antivirals reveals a novel non-nucleoside inhibitor of the viral polymerase

Abstract: Human norovirus causes approximately 219,000 deaths annually, yet there are currently no antivirals available. A virtual screening of commercially available drug-like compounds (~300,000) was performed on the suramin and PPNDS binding-sites of the norovirus RNA-dependent RNA polymerase (RdRp). Selected compounds (n = 62) were examined for inhibition of norovirus RdRp activity using an in vitro transcription assay. Eight candidates demonstrated RdRp inhibition (>25% inhibition at 10 µM), which was confirmed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 63 publications
(94 reference statements)
1
44
0
Order By: Relevance
“…Compound-induced toxicity of mammalian cells was assessed using CellTitre Blue (CTB) reagent (Promega, Madison, WI, USA), as previously described [19,42,43,44,45]. Briefly, CRFK (3.5 × 10 4 cells/well), RAW264.7 (2 × 10 4 cells/well) or Huh7 (5 × 10 3 cells/well) were seeded into 96-well plates and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound-induced toxicity of mammalian cells was assessed using CellTitre Blue (CTB) reagent (Promega, Madison, WI, USA), as previously described [19,42,43,44,45]. Briefly, CRFK (3.5 × 10 4 cells/well), RAW264.7 (2 × 10 4 cells/well) or Huh7 (5 × 10 3 cells/well) were seeded into 96-well plates and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of NITD008 on FCV and MNV infection was assessed by plaque reduction assays, as previously described [19,42,43,44,45]. Here, CRFK (8 × 10 5 ) or RAW264.7 (2 × 10 6 ) cells were seeded into each well of 6-well plates and incubated overnight for attachment.…”
Section: Methodsmentioning
confidence: 99%
“…To further exploit the broad‐spectrum RdRp binding pocket Site B, a high‐throughput in silico screen of approximately 300 000 commercially available compounds was performed to identify ligands that bind to Site B of the human norovirus and MNV RdRps . Sixty‐two compounds were selected from the screen and assessed for inhibition of the human norovirus RdRp, revealing a hit (compound 11 ) with an IC 50 of 5.0 µM.…”
Section: Drugs With Known Targetsmentioning
confidence: 99%
“…Synthesis of derivatives of this compound produced a novel candidate (compound 54 [2.2.10]) with IC 50 values of 5.6 µM (human norovirus RdRp) and 12.1 µM (MNV RdRp). Further in silico molecular modeling and biological antagonism studies with PPNDS suggested the binding site of compound 54 was indeed within the targeted broad‐spectrum Site B pocket, however, it was relatively ineffective against MNV in cell culture, with an EC 50 of more than 50 µM …”
Section: Drugs With Known Targetsmentioning
confidence: 99%
See 1 more Smart Citation